The Effect of Competency and Motivation on Performance with Job Satisfaction as an Intervening Variable at KJPP Abdullah Fiantoro and Partners - Firmansyah Firmansyah; Fadhilah Izhari; Cecep Haryoto (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to determine the level of Competency and Motivation on employee Performance with Job Satisfaction as an intervening variable at KJPP/ Public Appraisal Services Office. There are not many researchers who have looked closely at the Competency, Motivation, Job Satisfaction, and Performance at the Public Appraisal Services Office. Therefore, this research is considered essential to do. The research used a questionnaire that collected respondents from employees at KJPP Abdullah Fiantoro & Partners, Jakarta, Indonesia, and then analyzed using smartPLS with the SEM method. The results showed that Competency has a significant effect on Job Satisfaction, Motivation has a significant effect on Job Satisfaction, Motivation has a significant effect on employee Performance, and Job Satisfaction has a significant effect on Performance. On the other hand, indirectly, Competency through Job Satisfaction has a significant effect on Performance, and Motivation through Job Satisfaction also has a significant effect on Performance.